The vices of emperor Constans I in the fourth century histories - Milivojević Uroš (Zbornik Radova Vizantološkog Instituta, 2008)
The aim of this paper is to analyze the negative characteristics of the Roman emperor Constans I (337-350), according to the earliest preserved information from the late 4th century histories of Aurelius Victor, Eutropius Pseudo-Victor and Eunapius of Sardis. The earliest account of Constans' downfall is around 361 recorded by Aurelius Victor in his short history De Caesaribus. Victor wrote that Constans became more arrogant and aggressive after he defeated his elder brother Constantine II in 340. Also, he was not cautious enough for his young age, was hated due to his bad subordinates and did not respect his soldiers properly. But, the most outrageous fact was according to Victor, that the emperor had homosexual affinity towards his young and attractive barbarian hostages. The record of less moralistic Eutropius in his Breviarium ab Urbe condita, written in 369, is shorter but sharper. In the beginning the reign of Constans was vigorous and righteous but his character deteriorated after his illness. Following that, the young Augustus befriended himself with corrupted companions and turned to severe vices. His reign grew unbearable to his subjects and unpopular among the army ranks. Briefer then Eutropis is the testimony of an anonymous Latin author of Epitome de caesaribus who was contemporary to the Eastern Roman emperor Arcadius (395-408). This Pseudo-Victor wrote down that Constans devoted himself to hunting session, thus allowing plotters to dethrone him. Finally the single Greek author in this series, Eunapius (died after 404), whose istoria h meta Dexippon survived in fragments and Zosimus' late fifth century abridgment, called Constans the worst among the most intolerable tyrants. The Lydian sophist, as far as we could conclude from Zosimus', also recorded Constans' inclination towards young barbarians whom he allowed to mistreat his subjects. Because of wretchedness in the provinces of his realm, the courtiers led coup d'etat through Augustus' hunting session. Although vivid and informative, the real weight of these four accounts could be estimated only through comparison with the other, real or traditional, dreadful emperors described by the four authors. For example, the youthful age was important component of the bad reigns of Otho, Domitian and Gallienus, as Victor emphasizes. Eutropius' pattern of the promising start of the Emperor's reign and his later disgrace was similarly used in his assessment of Gallienus and Constantine the Great. According to Pseudo-Victor, Valentinian I could be estimated as the perfect prince if there had not been his poor selection of advisers. Constans' homosexual leaning towards young barbarian hostages could be observed from the two points. The first would be the remark that these barbarians were dubious companions for the Roman emperors, just as some of the rulers were blacklisted for their, real or assumptive, sympathy and meekness for women, eunuchs and courtiers. Gratian and Theodosius I were specially ill-famed for their affinity for Alan mercenaries and Gothic refugees respectively. On the other hand, slandered Licinius was praised for his strength in cultivating his courtiers and eunuchs. In relation to Constans' homosexuality, it is essential to note that one of the fundamental keys to the bad emperor's character was his breach of sexual taboos. In the inaccurate 4th century tradition Caracalla was known for his marriage with his stepmother, or Gallienus for his barter with Marcomanic king, in which he allegedly traded part of Pannonia Superior for the barbarian concubine. Explicitly, homosexuality was ascribed to Domitian, Carinus and Maximian Herculius. Finally, although the remarks on Constans' unpopularity and death were taken from the earliest preserved sources, it is clear that only a decade after his demise, the tradition, framed in already existing negative pattern, was established. This version of the events, probably maintained in lost Kaisergeschichte, was firstly acknowledged and then further supplemented by these four authors. In this context it is attractive to note down old samples of dire regimes and Roman historical tradition, still preserved both by the Latin and Greek authors in later 4th century. Then again, this fact is not very helpful in tracing the real character omissions of the deceased emperor Constans. .